Peningkatan Motivasi, Aktivitas, dan Hasil Belajar Biologi Melalui Penerapan Model Pembelajaran Numbered Head Together Pada Peserta Didik Kelas XI IPA 5 SMA Negeri 1 Masamba - Muliyati M; Rachmawaty Rachmawaty; Yusminah Hala; Oslan Jumadi (Universitas Negeri Makassar, 2017)
The research is a classroom action research which aims to discover the improvement ofmotivations, activities, and Biology learning results with the implementation of Numbered HeadTogether learming model to the students of class XI IPA 5 at SMAN 1 Masamba. The data of theresearch on the students' learning motivation is obtained through the students' leamingquestionnaire which is fulfilled by the students at the end of each cycle. The data on the students'activities are obtained through the students' activities observation sheet which is fulfilled by theobservers in every meeting and the data of the research on the students' Biology leaming resultsare obtained from the score of evaluation test at the end of each cycle. The results of the researchof the utilization of cooperative learning model of Numbered Head Together type in DigestionSystem material class XI IPA 5 students at SMAN 1 Masamba in Luwu Utara District can improvethe students' learning motivation, can improve the students' activities, and can improve thestudents' learning results.